Approaching Ancient Greek Coastal and Inland Poleis in the Northern Peloponnese: New Research in the Microregions of Aigeira, Lousoi and Sikyon (2025)
This volume presents an interdisciplinary discourse on recent archaeological investigations at the ancient sites of Sikyon, Aigeira and Lousoi. These three Northern Peloponnesian poleis represent microregions which from the Geometric and Archaic periods onward participated in similar networks of exchange, albeit with different roles. Dieser Band präsentiert einen interdisziplinären Diskurs über die jüngsten archäologischen Untersuchungen an den antiken Stätten von Sikyon, Aigeira und Lousoi. Die nordpeloponnesischen Poleis fungierten als Zentralorte dreier Mikroregionen, die seit der geometrischen und archaischen Zeit an ähnlichen Austauschnetzwerken partizipierten, wenn auch mit ganz unterschiedlichen Rollen.